Model Bahan Ajar Menulis Teks Biografi Pada Siswa Kelas X MA Riyadhus Sholihin - Sapitri, Merli; Nugroho, Agung (Linggau Jurnal Language Education and Literature, 2022)
ABSTRACT This study aims to develop teaching materials in the module of writing a biographical text. The development research method with the Addie development model is used to evaluate the biographical text writing module. The population and sample or research subjects are MA Riyadhus Sholihin students, to be precise in class X IPA. Data collection techniques in this study were interviews and questionnaires. While the data analysis techniques are validity and practicality tests. The results of the study prove that the module for writing biographical texts is very valid and practical. Design validation obtained an average V value of 0.825, language validation obtained an average V value of 0.75, and material validation obtained an average V value of 0.85. The conclusion of this research is that the module on writing biographical texts can be used as a learning resource that can be used in writing biographical texts.